PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH MATERI PENGURANGAN UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS II SEKOLAH DASAR - Khatimah, Husnul; Ananda, Niken; Salmanabila Pharsa, Azzahra; Risdalina, Risdalina; Destrinelli, Destrinelli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to improve student engagement in mathematics learning by implementing the “Pulau Pengurangan” board game as a learning media through the Cooperative Learning Model, Make A Match type. The classroom action research was conducted in grade II of SDN 111/1 Muara Bulian during April–May 2025, consisting of two cycles, each with two meetings. Data were collected through observations based on three indicators: enthusiasm in learning, willingness to answer questions, and effort to solve problems. The results showed a significant improvement in students' learning activity. Initially, in the pre-action stage, engagement was only 46.88%. After implementing the action, it increased to 55% in Cycle I (meeting II), and finally reached 70% in Cycle II (meeting II). This study concludes that using the Pulau Pengurangan board game effectively enhances students’ active participation in mathematics learning.